Dualism of Non Litigation Dispute Settlement in Sharia Economics at Basyarnas and Alternatif Dispute Resolution Agencies - Nurhasanah, Nurhasanah (Nurani, 2023)
The legal norms governing the resolution of sharia economic disputes in Basyarnas and LAPS OJK have created the legal dualism. it can be analyzed based on the choice of law, the choice of forum, and nature of the decision. This research uses normative legal methods to analyze problems qualitatively. It can be concluded that first, the dualism of resolving sharia economic disputes in Basyarnas and LAPS OJK can be seen from four aspects, namely legal sources, legal subjects, legal structures and legal facts. secondly, the POJK clause which requires the financial industry to become members of LAPS has violated the principles of choice of law and choice of forum of the parties. Third, Basyarnas' competence in resolving disputes by means of arbitration has had a legal relationship with the court to exercise executor authority, while the OJK LAPS has not. Apart from that, the OJK in this case seems very strong because apart from being a regulator, it is also an operator and even interferes with the duties and functions of the judicial power. The author suggests that legal unification is needed to create legal certainty.